Involvement of rapid nucleotide synthesis in recovery from phosphate starvation of Catharanthus roseus cells - Yin, Yuling (Journal of experimental botany, 2007)
Growth of suspension-cultured Catharanthus roseus cells ceased during phosphate starvation, but the cells grew again upon addition of Pi even after long-term starvation. The metabolic fate of [(33)P]Pi was studied in 1-week-old stationary phase cells in ordinary culture and in 1- or 2-week-old Pi-starved cells. Immediately after administration, the most heavily labelled organic compounds are nucleotides, followed by sugar phosphates. Two weeks Pi starvation slowed down the speed of incorporation of (33)P into nucleotides. The RNA, protein, and free nucleotide content all decreased gradually during Pi starvation; however, these compounds, especially nucleotides, increased markedly in the 24 h after addition of Pi. These responses are found in all cells examined, although the total amounts of these compounds were lower in the long-term Pi-deficient cells. Of the nucleotides, a marked increase was observed in nucleoside triphosphates and UDP-glucose. The transcript level of phosphate transporter and the activities of acid phosphatase, 5'- and 3'-nucleotidase, and adenosine nucleosidase were all reduced by the addition of Pi. In contrast, the activities of adenine phosphoribosyltransferase, nicotinate phosphoribosyltransferase, and nicotinamidase, which are salvage enzymes of purine and pyridine nucleotides, were markedly increased in the Pi-fed cells. Little or no increase was observed in adenosine kinase. In the light of these results, the possible involvement of net nucleotide synthesis in the initial metabolic events of recovery from Pi deficiency are discussed